APLIKASI TEORI VIRGINIA HENDERSON PADA PENGKAJIAN KEPERAWATAN PASIEN DENGAN UROLITHIASIS - Muhammad Putra Ramadhan; Agung Waluyo; Masfuri Masfuri (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Bengkulu, 2022)
Urolithiasis is a stone formation in the urinary tract that includes kidney stones, ureter stones, bladder calculi, and urethra. Urolithiasis is a disease of the urinary system that occupies the third position, where the prevalence reaches 10% and continues to increase in recent decades. Virginia Henderson proposes a theory of basic human needs that is appropriately used as the basis for the nursing assessment. The study aims to illustrate the application of Virginia Henderson's theory for nursing assessment in patients with urinary system disorders. The method used is a case study with an instrument based on 14 domains of basic human needs according to Virginia Henderson's theory. The results of the study showed there are basic needs that are problematic including eating and drinking needs, self-protection and hygiene, a sense of security and comfort, relaxation, and health services. Analysis of the data group with the Standard Diagnosis Keperawatan Indonesia obtained four nursing diagnoses each preoperative and postoperative phase. The results of the study showed that the application of Virginia Henderson's theory to patients with urolithiasis found 5 basic needs that had problems, there is eating and drinking, protection and personal hygiene, a sense of security and comfort, relaxation, and health services. In addition, Virginia Henderson's theory approach can be used as an assessment model, especially in the case of the urinary system. Further studies are needed to obtain a standard form of nursing assessment model based on Virginia Henderson's theory of basic needs.